Mulheres trabalhadoras em empreendimentos de economia solidária no norte mineiro - Ramos, Alyson Thiago Almeida (2012)
In recent years, it has grown the participation of women workers in grassroots initiatives to generate employment and income, based on associations and on principles of solidarity, cooperation and self-management. These initiatives, called the referenced field of Economic Development, are promoted as alternatives labor and social inclusion. The aim of this study was to investigate the inclusion of women in three experiments solidarity economy in the northern mining. We sought to examine to what extent this format work provides access to a regular income as the possibility of gains autonomy, recognition, qualification and self esteem / dignity. The study revealed that the groups studied undergo a series of shortcomings and are in a stage of dependence of incubation. The income gained for workers, not allowed an effective change in the output of poverty and precariousness, although significant improvements are seen. The changes in the sexual division of labor within and outside of workspaces, yet are barely noticeable. At another level, the impact of these experiences manifest themselves in strengthening social ties and belonging and social inclusion.